2012
DOI: 10.1007/s12192-012-0338-2
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of HspA1A with TLR2 and TLR4 in the response of neutrophils induced by ovarian cancer cells in vitro

Abstract: Inducible heat shock protein (HspA1A) promotes tumor cell growth and survival. It also interacts with effector cells of the innate immune system and affects their activity. Recently, we showed that the direct contact of ovarian cancer cells, isolated from tumor specimens, with neutrophils intensified their biological functions. Our current experiments demonstrate that the activation of neutrophils, followed by an increased production of reactive oxygen species, by cancer cells involves the interaction of HspA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…4a ). Furthermore, many genes known to regulate survival of different epithelial cell types are present in that list, including Sgk1 , Id1 , Vdr , Bcl2l14 , Dusp1 , Bmx and Igfbp3 (mammary gland), Pgf , Irf5 , Pla2g4a and Pmepa1 (intestine), and Hspa1a (ovary) 34 35 36 . Finally, several members of key pathways regulating cell survival/death were among sexually dimorphic genes: heat shock proteins ( Hspa1a , Hspa1b , Hspa2 , Hspb1 ) and members of the p53 ( Rnd3 , Plk2 , Sgpl1 , Igfbp3 , Pmepa1 ), Pi3k/Akt ( Pik3r1 , Pdgfc , Fn1 ) and Fas/caspases pathways ( Mcl1 , Hspa1b , Fn1 , Bcl2l14 , Lum ).…”
Section: Resultsmentioning
confidence: 99%
“…4a ). Furthermore, many genes known to regulate survival of different epithelial cell types are present in that list, including Sgk1 , Id1 , Vdr , Bcl2l14 , Dusp1 , Bmx and Igfbp3 (mammary gland), Pgf , Irf5 , Pla2g4a and Pmepa1 (intestine), and Hspa1a (ovary) 34 35 36 . Finally, several members of key pathways regulating cell survival/death were among sexually dimorphic genes: heat shock proteins ( Hspa1a , Hspa1b , Hspa2 , Hspb1 ) and members of the p53 ( Rnd3 , Plk2 , Sgpl1 , Igfbp3 , Pmepa1 ), Pi3k/Akt ( Pik3r1 , Pdgfc , Fn1 ) and Fas/caspases pathways ( Mcl1 , Hspa1b , Fn1 , Bcl2l14 , Lum ).…”
Section: Resultsmentioning
confidence: 99%
“…Hsp70 could increase tumor cell invasiveness through its ability to trigger an inflammatory tumor microenvironment. Besides activating antigen-presenting cells (APCs), free extracellular Hsp70 released from ovarian cancer cells has been shown to activate neutrophils and subsequent reactive oxygen species (ROS) production via TLR2/4 signaling [ 173 ]. ROS promote angiogenesis and metastasis via stimulation of vascular endothelial growth factor production [ 174 ] and activation of MMPs [ 175 ].…”
Section: Extracellular Functions Of Hsp70mentioning
confidence: 99%
“…TLR4 can mediate MyD88-dependent pathways through the interaction with a series of cytokines to promote tumorigenesis ( 31 ). Clinical studies also found that TLR4 was correlated with the growth and metastasis of gastric cancer ( 32 ), ovarian cancer ( 33 , 34 ), cervical cancer ( 35 ), and other types of tumor cells. In our study, we found that TLR4 was positively expressed in 58.33% cases of breast cancer tissues and in 90.57% cases of adjacent non-cancerous tissue.…”
Section: Discussionmentioning
confidence: 99%